EVALUATING THE EFFECTIVENESS OF BLOCK CHAIN TECHNOLOGY IN ENHANCING THE SECURITY OF DIGITAL FINANCIAL DATA: A CASE STUDY ON A SAMPLE OF COMMERCIAL BANKS OPERATING IN IRAQ - Ghaith Majid Hameed; Kadhim Abed Leethan (Scholars Digest Publishing, 2025)
This study uses a case study of a sample of Iraqi commercial banks to assess how well block chain technology can improve the security of digital financial data. Since conventional security measures are no longer adequate, the study is crucial in addressing the pressing need to create security systems to thwart cyberattacks that jeopardize the integrity of digital financial data. "There is a statistically significant effect of the effectiveness of block chain technology in protecting digital financial data," is the main hypothesis that the study tests. The deductive and inductive methods were used by the researchers, and a sample of forty-five employees of Al-Taif Islamic Bank and Al-Janoub Islamic Bank were used in the study. The statistical findings support the alternative hypothesis by showing that block chain technology directly and significantly improves the security of digital financial data. Block chain characteristics, the independent variables, account for 81% of the variance in the dependent variable (digital financial data security), indicating that the model effectively depicts the phenomenon under study. The results showed that the features of the technology, like immutability, which bars alteration and deletion, and decentralization, which prevents a system breach all at once, are a fundamental approach to security problems. By contrast, scalability is one of the primary barriers to the technology's implementation in banks. The researchers advise banks to prioritize high-speed processing solutions to overcome the scalability issue and carefully incorporate blockchain technology into their current security infrastructure.
Keywords: Block chain technology; Digital financial data security; Commercial banks; Iraq; Financial security; Case study; Banking sector; Data integrity.